Cultura jovem na cidade de Vitória/ES : as práticas corporais juvenis e sua relação com a educação física escolar - Bungenstab, Gabriel Carvalho (2013)
This essay tries to understand some of the facets of the young people who attend High School in the city of Vitória, capital of Espírito Santo, establishing body practices as a reference. For this purpose, this dissertation organizes itself in two distinct moments, the first one holds as a conceptual characteristic, an opportunity to realize a reading about the modern society (and contemporary) from the work of the sociologists Zygmunt Bauman and Michel Maffesoli. Both the sociologists are utilized as to help the comprehension of the youth in modern society. The second moment of this word is composed by what I define as three ethnographic incursions. In the first ethnographic incursion I make use of an open questionnaire and perform a mapping of the 13 High School institutions located in the city of Vitória, the goal is to identify the body practices that the young people have been carrying on in and outside of school. The second ethnographic incursion is dedicated to analyzing the Jogos na rede and Cultura em rede events which occurred in the city of Guarapari, a municipality of Grande Vitória, when I accompanied young people who took part in the fore mentioned events. At this point I emphasize the juvenile relations built during the event as well as how the sportive manifestations are seen and treated by the youth. The third (and last) ethnographic incursion was employed at a single school, from February to September of 2012. Focusing at only one school, I intended to work in a deeper level some issues and themes that were identified when the questionnaire from the first ethnographic incursion was implemented. This would be an opportunity to discuss once more the relations between Physical Education and the culture of the youth and its body practices on High School, in and out of school. Finally, the research has shown how the young people delegate importance to the body practices, either be them held in or outside the school environment, suggesting that at contemporary times it isn t possible to think about the youth without regard to their body practices